Family aggression in a social lizard - Botterill-James, T; Halliwell, B; McKeown, S; Sillince, J; Uller, O; Wapstra, E; While, G (Springer Nature, 2017)
The evolution of family living is underpinned by conflict and cooperation between family members. While family groups can be maintained by reducing conflict between parents and offspring, interactions between siblings may play an equally important role. Here, we compared the level of aggressive interactions between siblings to that between parents and their offspring in the family living skink Liopholis whitii. Aggressive interactions occurred much more frequently between siblings and between fathers and offspring than between mothers and their offspring. These results suggest that ecological and social conditions that reduce conflict between siblings and between males and offspring will be fundamental in the evolutionary maintenance and diversification of family living in these lizards.